INF2‐ and FHOD‐related formins promote ovulation in the somatic gonad of C. elegans. Issue 12 (December 2016) - Hegsted, Anna; Wright, Forrest A.; Votra, SarahBeth; Pruyne, David
Abstract : Formins are regulators of actin filament dynamics. We demonstrate here that two formins, FHOD‐1 and EXC‐6, are important in the nematode Caenorhabditis elegans for ovulation, during which actomyosin contractions push a maturing oocyte from the gonad arm into a distensible bag‐like organ, the spermatheca. EXC‐6, a homolog of the disease‐associated mammalian formin INF2, is highly expressed in the spermatheca, where it localizes to cell‐cell junctions and to circumferential actin filament bundles. Loss of EXC‐6 does not noticeably affect the organization the actin filament bundles, and causes only a very modest increase in the population of junction‐associated actin filaments. Despite absence of a strong cytoskeletal phenotype, approximately half of ovulations in exc‐6 mutants exhibit extreme defects, including failure of the oocyte to enter the spermatheca, or breakage of the oocyte as the distal spermatheca entrance constricts during ovulation. Loss of FHOD‐1 alone has little effect, and we cannot detect FHOD‐1 in the spermatheca. However, combined loss of these formins in double fhod‐1;exc‐6 mutants results in profound ovulation defects, with significant slowing of the entry of oocytes into the spermatheca, and failure of nearly 80% of ovulations. We suggest that EXC‐6 plays a role directly in the spermatheca, perhaps by modulating the ability of the spermatheca wall to rapidly accommodate an incoming oocyte, while FHOD‐1 may play an indirect role relating to its known importance in the growth and function of the egg‐laying muscles. © 2016 The Authors. Cytoskeleton Published by Wiley Periodicals, Inc.